Efeito da silimarina e silibinina sobre as alterações comportamentais e neuroquímicas induzidas por 6-hidroxidopamina em camundongos - Freitas, Catiuscia Molz de (2018)
Parkinson's disease (PD) is a disabling neurodegenerative disease that affects about 1-2% of the world's population. L-dopa is the most used treatment to attenuate the symptoms of PD; however, in the long term this drug leads to fluctuations in clinical response and the emergence of dyskinesias, it becoming necessary the search for new therapeutic strategies. In this sense, silymarin, isolated from the seeds of Silybum marianum and silibinin, its major constituent, are bioactive substances that have demonstrated antioxidant and neuroprotective effects. Thus, the objective of this study was to investigate the effects of silymarin and silibinin on the behavioral and neurochemical alterations induced by 6-hydroxydopamine (6-OHDA) in mice, in addition, we evaluated the effect of co-treatment with silymarin and L-dopa. Firstly, the animals received an intracerebroventricular (i.c.v.) injection of 6-OHDA (60 μg) or vehicle (saline containing 0.05% ascorbic acid). After 7 days, was started the treatment with different doses of silymarin (10, 30 or 100 mg/kg) by via intraperitoneal (i.p.) for 7 days. Behavioral evaluations were performed on days 8 and 15 of the experimental period. 6-OHDA caused a motor impairment in the animals, which was accompanied by a reduction in tyrosine hydroxylase (TH) immunoreactivity and an increase in phospho-ERK1/2 in both striatum and substantia nigra. Silymarin treatment recovered the motor coordination of the animals without changing in the phospho-ERK1/2. In the substantia nigra, silymarin at the dose of 30 mg/kg restored changes in TH induced by 6-OHDA. In addition, it was evaluated the effect of silibinin on the 6-OHDA model, where the animals received an i.c.v. injection of 6-OHDA or vehicle. After 7 days it was started the treatment with different doses of silibinin (50 or 100 mg/kg, i.p.) during 7 days. 6-OHDA induced a motor dysfunction that was accompanied by a reduction in TH immunoreactivity in the striatum. Silibinin recovered the motor balance of the animals evaluated on the beam walk test as well as modified the TH levels. In the sequence, it was investigated the effect of co-treatment with silymarin and L-dopa on the 6-OHDA model. Seven days after administration of 6-OHDA or vehicle was started the treatment with silymarin (30 mg/kg, i.p.) and/or L-dopa (25 mg/kg, i.p.) plus benserazide (10 mg/kg, i.p.) for 28 days. Treatment with silymarin recovered the locomotor activity of the animals; although the co-treatment with silymarin did not potentiate the effect of L-dopa on motor damage caused by 6-OHDA. Furthermore, concomitant treatment with silymarin and L-dopa seems to antecipate the emergence of dyskinesia, observed by an increase on the number of vacuous chewing movements (VMCs). On the day 36, apomorphine (1 mg/kg) was administered and locomotion and stereotypy of the animals were evaluated. However, no significant differences were observed in locomotion and in stereotypy of animals. The results suggest the effect of silymarin in the 6-OHDA model is possibly due to the synergism of all its components and not only the action of its major constituent, silibinin. Thus, silymarin could be a promising therapeutic agent in the initial treatment for mild parkinsonian symptoms. However, silymarin should be better studied before it is used as an adjunct to L-dopa therapy, since their association seems to precipitate the emergence of dyskinesia in mice.